Afinando los acordes de la identidad juvenil: Un proyecto de comunidad enfocado en la música en Inglés (GIST – Education and Learning Research Journal, 2019)
This is an exploratory case study implemented in a public school of Ibagué Colombia, that reports findings of a qualitative research. In this study tenth graders EFL students, explored into their local contexts, salient aspects of youth identity, that emerged from interaction with music in English. The study is framed on some basic principles of Critical Pedagogy (CP) and foundations of Community- Based Pedagogies (CBP). Content data analysis was used to examine the information obtained from the different tools of data collection: community mapping, questionnaires, recorded semi-structured interviews and notes in the teacher’s journal. Finally, member checking was implemented to validate data and to increase the credibility and validity of this qualitative study. Conclusions and pedagogical implications reveal how local inquiries focused on music in English become a source for language learning and enlighten curriculum designers and teachers towards the construction of a flexible curriculum with relevant content, oriented to youth identity exploration and understanding
Keywords: Identidad; Pedagogía basada en la comunidad; Pedagogía Crítica; Música como herramienta pedagógica